2019
DOI: 10.1093/ibd/izz253
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Medication Nonadherence to Self-Injectable Biologic Therapy in Adult Patients With Inflammatory Bowel Disease

Abstract: Background In inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), nonadherence to biologic therapy increases risk of disease flare. The aim of this study was to identify risk factors for nonadherence. Methods This was a single-center retrospective study evaluating patients with IBD treated at a tertiary care center and prescribed self-injectable biologic therapy using the center’s spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
2
20
1
Order By: Relevance
“…In another study, age over 18 years was associated with a better knowledge of diagnosis and medication names than age under 14 years (94% and 89% compared with 45% and 58%, respectively). Similar to our study, others also reported 38%‐66% of medication non‐adherence in paediatric‐onset IBD, whereas adults show a better adherence to the treatment (69%‐82%) . A structured transition service was perceived as very important by 80% paediatric gastroenterologists, while 79% of adult gastroenterologists identified inadequacies in the preparation for transfer .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In another study, age over 18 years was associated with a better knowledge of diagnosis and medication names than age under 14 years (94% and 89% compared with 45% and 58%, respectively). Similar to our study, others also reported 38%‐66% of medication non‐adherence in paediatric‐onset IBD, whereas adults show a better adherence to the treatment (69%‐82%) . A structured transition service was perceived as very important by 80% paediatric gastroenterologists, while 79% of adult gastroenterologists identified inadequacies in the preparation for transfer .…”
Section: Discussionsupporting
confidence: 85%
“…Our findings, strengthened by the mentioned above studies, reinforce the importance of adopting a structured transition plan and assessment of transition readiness in IBD centres and may suggest that the transition process should begin at an older age with engagement of patient, their parents and treating physicians to this process …”
Section: Discussionsupporting
confidence: 77%
“…In a recent single-centre study from the USA, a retrospective analysis revealed that 69% of patients were adherent to the self-injectable biologic. 43 In a study evaluating adherence to an oral drug [5-ASA] in quiescent/mildly active UC, patients identified that baseline non-adherence was 52.4%. Even an educational effort was unable to increase the rate of adherence.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Furthermore, previous studies have found chronic opioid use in IBD is associated with worse surgical outcomes, longer hospital stays and increased mortality 8,9 . Many predictors of chronic opioid use are associated with poorer outcomes in IBD such as smoking, depression and therapeutic non‐compliance 5,10 . We suspect that chronic opioid use may further interfere with productive therapy by enhancing patient behaviours that compromise effective clinical management.…”
Section: Introductionmentioning
confidence: 99%